Dismantling spaces of silence in social science education - Claravall, Eric B.; Ferreras-Stone, Jessica (Social Science Education Consortium book series., 2024)
Throughout history, silences have been an inherent process of historical production - privileged narratives masquerade as definitive history, and those deemed less worthy are mute (Trouillot, 1995). Because of this, our understanding of many events in the past is incomplete; and the way we frame our contemporary societies based on these events is, implicitly or explicitly, silenced by inherently racist structures. The editors of this volume define spaces of silence beyond the temporality and physicality of historical events. Spaces of silence exist within minds, emotions, systems, and places. For instance, we recognize ways in which settler colonialism historically and presently silences Indigenous sovereignty and rights to place.How do we, then, dismantle these spaces in a multi-racial society and globalized world? Dismantling these spaces of silence situates hopes and possibilities of decolonizing our ways of thinking, ways of acting, and ways of being. This volume seeks work that calls out the various spaces of silence and ways to dismantle these spaces.